PREPARATION AND PROPERTIES OF COPPER COMPLEXES CHELATING LIGANDS - Angulo Cornejo, J. (1999)
n 1999, global copper production is based on a 80 % in low-grade ores , the metal content is below 2 %. This has focused research efforts - to develop alternative ways to cough pyrometallurgical processes such as hydrometallurgical extraction processes . Since the advent of the first commercial extractants in markets 30 years ago (LIX 63 ), research was directed towards the study of properties such as selectivity , kinetics and solubility at different pH values ​​. Copper, due to its electronic configuration and their different oxidation states , complexes in which the ligands have to have specific selectivity and stability in the organic phase. In the experimental part of this work , complexes of Cu ( I) and Cu ( II ) with anionic and neutral chelating ligands according to their electrochemical properties were studied.